(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Faba bean (Viciafaba L.) is subjected to drought stress duringdifferent growth stages. In this study, variability in seed yield and proteincontent was investigated when drought occurred during the vegetative andreproductive stages. Twenty-two genotypes of faba bean were field-evaluated under three levels of drought stress at two locations in theSudan. The three levels of drought were normal watering (non-stress),drought during the vegetative stage and drought during the reproductivestage. Data were collected on yield and vegetative traits and proteincontent. The results showed that yield, as well as other traits, werereduced by drought. The genotypes exhibited significant differences for100-seed weight, plant height and protein content. The interactionbetween the genotypes and drought was significant for yield/plant. Somegenotypes were more sensitive when drought occurred during thevegetative stage, some when drought occurred at the reproductive stage,and others were more stable under the three levels of drought. Yield/plantshowed significant covariance with pods/plant and plant height. Theassociation between different characters varied according to the trait andthe time of drought incidence. The correlation of yield/plant with proteincontent was negative under all drought levels, and the average correlationcoefficient was - 0.32. It could be concluded that the specific adaptation